Salinity-induced accumulation of organic osmolytes in barley and wheat leaves correlates with increased oxidative stress tolerance in planta evidence for cross-tolerance - Puniran-Hartley, Norhawa (Plant physiology and biochemistry : PPB, 2014)
Copyright © 2014 Elsevier Masson SAS. All rights reserved.